School bullying victimization: A public health issue - Karanikola, Maria; Zavrou, Rafailia; Hatziioannou, Anna (My University, 2018)
© 2018, Hellenic Nurses Association. All rights reserved. Background: Bullying victimization and harassment exists over time in most forms of social organization, including school environment. Research data show a link between school bullying victimization and physical, mental and social adverse phenomena. Objective: The present article presents a description of school bullying victimization, including possible adverse effects, as well as risk and protective factors, and interventions for effective management in personal and social level. Material and Method: A literature review was conducted on both Greek and English languages, through Pubmed, Scopus, Science Direct?a? Google Scholar databases, using the key-words: “Intimidation”, “School Environment”, “Physical and Psychological Violence”. Results: School bullying victimization seems to reflect a problem mainly associated with the organizational and administrative parameters of the school milieu, and mostly the social structure of it, rather than personal characteristics. Bullies come from both sexes, characterized by their need to dominate others, aiming to cause physical or psychological pain to the victims. The impact of school bullying victimization includes neuro-cognitive and psychological disturbances such as decreased self-esteem, anxiety symptoms and panic attacks, depressive symptoms, self-harming and suicidal behaviour (suicidal ideation and suicidal attempts), substance abuse and mental health problems in adult life. Despite the severity of suffering, the victims of school bullying are reluctant to contact their parents or teachers regarding this phenomenon. The main reasons for this comprise feelings of shame, fear of retaliation, or the fact the bullies, in most cases, have “convinced” the victims that they are “omnipotent”, thus no one is able to help them. The children who may become victimized, most of the times, have any kind of: (a) weakness or disability, (b) diversity in physical appearance, religion, race, ethnicity and sexual orientation, (c) mental problems or learning disabilities, e.g. attention deficit and hyperactivity disorder, or (d) are eminent for their excellence. Conclusions: The interplay between school context factors and individual characteristics seems to influence both the risk for involvement in bullying and the impact of it. Overall, school administrative policies are required to promote a safe and supportive environment for children of all ages. Health-care professionals, including school nurses and mental health nurses, along with those involved in policy making and education process need to recognize the importance of supporting school students, as well as developing interventions targeted to re-formation of school context when relevant issues arise. Effective prevention and management of school bullying involves a structured public health approach, encompassing multiple levels of intervention, i.e. individual, classroom and school, as well as family and community based interventions.
Keywords: Intimidation; Physical and psychological violence; School environment